Effect of dynamic high pressure microfluidization on structure and stability of pluronic F127 modified liposomes. Issue 7 (3rd July 2019) - Li, Ziling; Peng, Shengfeng; Chen, Xing; Zhu, Yuqing; Zou, Liqiang; Zhou, Wei; Liu, Wei; Liu, Chengmei
Abstract: Pluronics modified liposomes have been prepared and shown to enhance stability of liposomes in our previous reports. In this study, we intended to evaluate the effect of dynamic high pressure microfluidization (DHPM) on the structure and stability of pluronic F127 modified liposomes. The results indicated that the particle size of F127 modified liposomes was decreased from 1180.6 nm to 73.5 nm after DHPM treatment. Meanwhile, the morphology was changed from irregularly multilamellar vesicle to spherically unilamellar structure. Structural characteristics were examined by fourier transformed infrared spectrometer, differential scanning calorimetry and X-ray powder diffraction. The subtle difference of structure might be attributed to the incorporation of PPO chains into the bilayer caused by DHPM treatment. Stability studies indicated that DHPM treatment could enhance the storage and membrane stability of F127 modified liposomes. This study may provide more insight to understand the effect of preparation method on the structure and stability of F127 modified liposomes. Graphical Abstract: uf0001